2004
DOI: 10.1088/0960-1317/14/12/005
|View full text |Cite
|
Sign up to set email alerts
|

Polymer deformation and filling modes during microembossing

Abstract: This work investigates the initial stages of polymer deformation during hot embossing micro-manufacturing at processing temperatures near the glass transition temperature (Tg) of polymer films having sufficient thickness such that polymer flow is not supply limited. Several stages of polymer flow can be observed by employing stamp geometries of various widths and varying imprint conditions of time and temperature to modulate polymer viscosity. Experiments investigate conditions affecting cavity filling phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 16 publications
6
66
2
Order By: Relevance
“…[10][11][12][13][14] On the other hand, confinement will also directly impact the flow pattern. This parameter is prominent in a number of numerical studies of embossing 15,16 but there is still a good deal of confusion over this issue. On the one hand, some studies of NIL reflow 17,18 completely neglect the direct impact of confinement on flow rate.…”
mentioning
confidence: 99%
“…[10][11][12][13][14] On the other hand, confinement will also directly impact the flow pattern. This parameter is prominent in a number of numerical studies of embossing 15,16 but there is still a good deal of confusion over this issue. On the one hand, some studies of NIL reflow 17,18 completely neglect the direct impact of confinement on flow rate.…”
mentioning
confidence: 99%
“…Elastic solid simulations modeled the polymer with the nonlinear stressstrain behavior of a Moony-Rivlin material. The studies showed both single and dual peak flow confined near the master sidewall as described above [6,7], and noted the effect of film thickness to retard deformation. The authors concluded that polymer in NIL shows rubber-like elastic dynamics above T g with volume compression under high loads in thick polymer films, suggesting that the elastic component of polymers plays a large role in deformation even at temperatures well above T g .…”
Section: Introductionmentioning
confidence: 72%
“…These simulations showed the buckling region was the result of capillary forces acting over the large cavity width, where the polymer preferentially wetted the master surface. When surface tension effects were removed from the simulations, smooth single or dual peaks were observed dependent on cavity width, as observed in viscous flow experiments [6]. Other simulations and experiments [10,11] investigated purely nanometer scale geometries and film thicknesses.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Figure 4 showed some typical hot embossing results. The filling mechanism of the cavity was a single-peak mode rather than the dual-peak mode reported in some studies (Heyderman et al 2000;Rowland and King 2004). In the dual-peak mode, the phenomenon was seen under a two-dimensional surface profilometric scan, as two peaks climbing up the cavity walls.…”
Section: Multi-layer Microelectrofluidic Platformmentioning
confidence: 84%